Antenatal Selenium Deficiency Decreases Neonatal Pulmonary Selenium-Containing Antioxidant Enzymes. (7th June 2021) - Balasubramaniyan, Durganili; Zheng, Lijun; De Dios, Robyn; Nozik, Eva; Wright, Clyde; Sherlock, Laura
Abstract: Objectives: Bronchopulmonary dysplasia (BPD) is the most common complication of prematurity. Selenium (Se) deficiency increases the risk for oxygen requirement at 28 days and BPD and thus may be a modifiable nutritional intervention. Se is an essential trace mineral that is incorporated into Se-containing antioxidant enzymes (AOE). An infant's Se status at birth is regulated by the mother's Se supply during pregnancy, however, it is unknown if any neonatal Se-containing AOE in the lung are decreased by antenatal Se deficiency. We hypothesize that antenatal Se deficiency will decrease neonatal pulmonary expression of Se-containing AOE. Methods: C57Bl/6 mice were allocated to sufficient (SeS, 0.4 ppm Se) or deficient (SeD, < 0.01 ppm Se) diets before breeding. Breeding pairs were allowed to serially breed, and pups from the 1 st -4 th pregnancies were evaluated. Pups were sacrificed at PN0. Glutathione peroxidase (GPx) activity was measured in the lung by enzyme activity assay. Pulmonary GPx1, GPx3, thioredoxin reductase 1 (Trxrd1) and selenoprotein N (SelenoN) protein content were measured by Western blot. F and M pups were analyzed as separate groups. Results: Weights were similar at postnatal day 0 (PN0) and PN4 for SeS and SeD pups, but by PN7 through adulthood, both male and female SeD mice weighed less then SeS mice. At PN0, pulmonary GPx activity was decreased in all SeD pups, with similar decreases in the protein content of both GPx1 and GPx3 (n = 6–10). We observed a progressive impact of SeD on the pups based on the dam's pregnancy. GPx activity and protein contents were more significantly decreased in pups born after a dam's 3 rd or 4 th pregnancy than the 1 st or 2 nd (n = 4–6). Trxrd1 and SelenoN protein content were not decreased in pups born after a dam's 1 st or 2 nd pregnancy (n = 4–6). However, both were decreased in the lungs of pups born to a dam's 3 rd or 4 th gestation (n = 6). Conclusions: Neonatal pups exposed to antenatal SeD demonstrate decreased pulmonary GPx protein content and activity level without sex differences. Pups born to a SeD dam's third or fourth gestation exhibited a further decline in pulmonary Trxrd1 and SelenoN content. We speculate that SeD neonates may be vulnerable to pulmonary oxidative stresses secondary to low antioxidant enzymatic defense. Impaired ability to respond to oxidative challenge in the lung may predispose SeD infants to BPD. Funding Sources: NIH/NHLBI.